Modifying nanoparticle shape by choice of synthetic method: nanorods, spheres, mutipods, and gels - Shrestha, Khadga M. (Kansas State University, 2012)
A series of nanoparticle synthesis methods were devised with the aim of controlling shape. CuO nanorods were synthesized by a hydrothermal treatment with different chemical combinations. Physical parameters: concentration, temperature, and aging time greatly affected the size, morphology and the composition of nanorods. These CuO nanomaterials were reduced to metallic copper at elevated temperature by 4% H[subscript]2 diluted in helium while preserving the morphology. The CuO and Cu nanomaterials were employed for near infra-red (NIR) diffuse reflectance. Among them, CuO nanorods were found to be the best NIR diffuse reflectors, indicating potential application as NIR obscurants. Cu[subscript]2O and its composite samples with different morphologies, some with unique morphologies, were synthesized by reducing Cu[superscript]2[superscript]+ precursors without using any surfactant. The effects of change of Cu-precursors, reducing agents, and other physical conditions such as temperature and pressure were investigated. Since Cu[subscript]2O is a semiconductor (E[subscript]g ~ 2.1 eV), these samples were used as photocatalyst for the degradation of methyl violet B solution under UV-vis light and as dark catalysts for decomposition of H[subscript]2O[subscript]2 to investigate the effect of morphology. The photocatalytic activity was found to be morphology dependent and the dark catalytic activity was found to be dependent on both surface area and morphology. Mixed oxides of MgO and TiO[subscript]2 with different ratios, and pure TiO[subscript]2 were synthesized by two methods—flame synthesis and aerogel. These mixed oxides were employed as photo-catalysts under UV-vis light to oxidize acetaldehyde. The mixed oxides with low content of MgO (~ 2 mole %) were found to be more UV active photo-catalysts for the degradation of acetaldehyde than the degradation by TiO[subscript]2. The mixed oxides prepared by the aerogel method were found to be superior photo-catalysts than the mixed oxides of equal ratio prepared by flame synthesis. Silica aerosol gels were prepared by two methods: detonation and flame synthesis. Hexamethyldisiloxane (HMDSO) was used as a precursor during the detonation at different conditions. Interestingly, spherical silica nanoparticles were found to be formed by the detonation. Relatively smaller silica nanoparticles with larger volume fraction were found to be favorable for the formation of silica aerosol gels. During the flame synthesis, the silicon precursors, dimethoxydimethylsilane (DMDMS) and HMDSO, were used. Different shapes—spherical, oval, and non-spherical—and sizes of silica particles were formed. These silica nanomaterials were almost amorphous, and they might have many potential applications.
Keywords: Nanomaterials; Chemistry (0485)